A Randomized Controlled Trial on the Influence of Prenatal Counseling on the Attitudes and Preferences Toward Invasive Prenatal Testing Among Women in Their First Trimester of Pregnancy (INVASIVE) - Paz y Miño, Fernanda; Martinez-Portilla, Raigam Jafet; Pauta, Montse; Borrell, Antoni (Frontiers in Genetics, 2020)
Objective To assess the impact of prenatal genetic counseling on the attitudes and preferences toward invasive testing in first-trimester pregnant women. Methods This is a randomized open-label study, of pregnant women undergoing first trimester combined screening for aneuploidies. Women were divided into the experimental or control groups in a 1:1 design. The intervention consisted of 15-min extra counseling about prenatal screening and diagnosis. The main outcome was the desire to choose an invasive testing as their first prenatal testing option which was measured as absolute risk. Results After excluding those with incomplete data, 75 women remained in the experimental group and 75 as controls. Women receiving counseling were 32% more likely to choose an invasive prenatal testing as their first-line option after extra 15-min extensive counseling, reducing the first-trimester combined screening by 20% and the cell-free DNA by 12%. If given the opportunity, 59% of the women would like to be able to choose the prenatal test that suits their needs. Conclusion Women given an extensive prenatal counseling are more likely to choose an invasive testing as their first-line test in spite of the concerning risks. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT04119349.